PROBLEMATIKA PENERAPAN ASAS RECKLESSNESS DALAM PERSPEKTIF PEMBAHARUAN HUKUM LALU LINTAS DI INDONESIA - Edi As'adi (Jurnal Dinamika Hukum, 2014)
Recklessness is one of the causes of traffic accidents. However, Law No. 22 of 2009 has not implicitly set the application of the principle of recklessness. So in field settings is still referring to the 359 of the Criminal Code, Article 360 of the Criminal Code and Article 492 of the Criminal Code, and even for difficult cases and found no law in the traffic law, judges apply article 338 of the Criminal Code with the principle of dolus eventualis consideration to fill the legal vacuum which are not in traffic law. Based in the future it is necessary reformulation of the principle of Recklessness in traffic law reform based on social justice values of Pancasila. Key words: legal, reckless, renewal, traffic.